2012 IEEE International Conference on Oxide Materials for Electronic Engineering (OMEE) 2012
DOI: 10.1109/omee.2012.6464738
|View full text |Cite
|
Sign up to set email alerts
|

Homogenous and heterogeneous magnetism in (Zn,Co)O

Abstract: A series of (Zn,Co)O layers with Co contents x up to 40% grown by atomic layer deposition have been investigated. All structures deposited at 160• C show magnetic properties specific to II-VI dilute magnetic semiconductors with localized spins S = 3/2 coupled by strong but short-range antiferromagnetic interactions resulting in low-temperature spin-glass freezing for x = 0.16 and 0.4. At higher growth temperature (200• C) metallic Co nanocrystals precipitate in two locations giving rise to two different magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 84 publications
(134 reference statements)
0
17
0
Order By: Relevance
“…It was found that formation of most of the oxides is enhanced at increased temperatures. Thus, a low growth temperature is highly profitable, as already indicated by Sharma and co-workers [5], and by us for both ZnMnO [15,28,29] and ZnCoO [24,30]. This is why in further studies we lowered a growth temperature by replacing zinc acetate with DEZn or DMZn precursors.…”
Section: Mnomentioning
confidence: 69%
See 4 more Smart Citations
“…It was found that formation of most of the oxides is enhanced at increased temperatures. Thus, a low growth temperature is highly profitable, as already indicated by Sharma and co-workers [5], and by us for both ZnMnO [15,28,29] and ZnCoO [24,30]. This is why in further studies we lowered a growth temperature by replacing zinc acetate with DEZn or DMZn precursors.…”
Section: Mnomentioning
confidence: 69%
“…Knowledge of the growth mode is not only academic. We found that this information is crucial to explain magnitude and anisotropy of the observed magnetization, as is discussed separately [30]. However, if low temperature processes of ZnO and ZnTMO deposition are required (to get uniform TM distribution, material suitable for hybrid structures with organic films, etc...), control of the growth mode is fairly difficult.…”
Section: Growth Modes Of Lt Zno Znmno and Zncoo Layersmentioning
confidence: 72%
See 3 more Smart Citations